2017
DOI: 10.7599/hmr.2017.37.1.18
|View full text |Cite
|
Sign up to set email alerts
|

The role of PI3K/AKT pathway and its therapeutic possibility in Alzheimer's disease

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/3.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.Alzheimer's disease (AD) is the most common form of dementia. Although uncountable clinical trials have been done to develop the treatment of AD, there are a couple of drugs that can be used only for symptomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 68 publications
(68 reference statements)
0
17
0
Order By: Relevance
“…Overactivity of GSK-3β promoted tau hyperphosphorylation and amyloid plaque formation [ 214 ]. Aβ oligomers can also inhibit the PI3K/Akt pathway, activating GSK-3β, causing neurotoxicity [ 215 ]. Meanwhile, in PD, there is a significant decrease of Akt expression with the loss of dopaminergic neuron compared to control [ 216 ].…”
Section: Oxidative Stress and Intracellular Signaling Pathwaymentioning
confidence: 99%
“…Overactivity of GSK-3β promoted tau hyperphosphorylation and amyloid plaque formation [ 214 ]. Aβ oligomers can also inhibit the PI3K/Akt pathway, activating GSK-3β, causing neurotoxicity [ 215 ]. Meanwhile, in PD, there is a significant decrease of Akt expression with the loss of dopaminergic neuron compared to control [ 216 ].…”
Section: Oxidative Stress and Intracellular Signaling Pathwaymentioning
confidence: 99%
“…Experimental evidence indicated that protein kinase B (Akt) is a pivotal survival signal molecule mediating anti-apoptosis and cell survival. Two mitochondrial proteins are phosphorylated following stimulation of mitochondrial Akt, the β-subunit of ATP synthase and GSK-3β, an important and well-known protein involved in the direct induction of tau phosphorylation in AD, which leads to cell death [34]. In addition, the survival phosphatidylinositol 3-kinase (PI3K/Akt) pathway modulates mammalian target of rapamycin (mTOR) kinase activity, which is also altered in neurodegenerative diseases accompanied by cognitive deficits (AD, PD) due to its implication in the regulation of a broad range of cellular processes, including survival, proliferation, growth, and migration of cells [34,35].…”
Section: Survival Signaling Pathwaysmentioning
confidence: 99%
“…Two mitochondrial proteins are phosphorylated following stimulation of mitochondrial Akt, the β-subunit of ATP synthase and GSK-3β, an important and well-known protein involved in the direct induction of tau phosphorylation in AD, which leads to cell death [34]. In addition, the survival phosphatidylinositol 3-kinase (PI3K/Akt) pathway modulates mammalian target of rapamycin (mTOR) kinase activity, which is also altered in neurodegenerative diseases accompanied by cognitive deficits (AD, PD) due to its implication in the regulation of a broad range of cellular processes, including survival, proliferation, growth, and migration of cells [34,35]. The fact that the activation of mTOR is related to the presence of soluble Aβ and tau protein reveals the role of mTOR as one of the mechanisms involved in Aβ-induced toxicity in AD and indicates the potential of mTOR modulators as effective agents in the prevention of these pathologies [36].…”
Section: Survival Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, he described the importance of the signaling pathway in AD. His review will improve readers' understanding on the relationship between the PI3K/Akt pathway and AD [3]. Fourth, Dr. Jung who is an expert on otology wrote cutting edge technologies on the otology field and reviewed their usefulness for patients with ear problems [4].…”
mentioning
confidence: 99%